Characteristics of Sand at Major Quarrying Areas around Addis Ababa - Daniel Shewatatek; Belestie Tenaw; Asratie Yemiru; Gebrehana Belete; Tena Tadesse; Tamiru Tolla (Advances in Civil Engineering)
This study focused on the measurements of physical and chemical characteristics of sand samples taken from Atayie, Je-wuha, Ziway (4 quarrying sites), Mekie (4 quarrying sites), and Soderie (2 quarrying sites) were analyzed by conducting different tests, such as silt content, moisture content, bulking, sieve size, unit weight, specific gravity, water absorption, and organic impurities tests. After conducting those tests, the results of sand samples taken from Atayie, Je-wuha, Alagie, and Bosat Fokie sites satisfied 100% test standard requirements. In the same way, Kiera and Atie leman sand sample satisfies the 90% test requirement while Lolie basuma sand satisfies 80% test requirements and Endala chebie satisfies 70% among 10 tests with respective requirements. However, the result of sand samples taken from Langano, Godo, Melka Jelo, and Dehera Degaga satisfies below 50% of the tests among the 10 test parameters.